Tabla de contenidos (European Journal of Education and Psychology, 2022)
IntroductionCurrent status of research on social anxiety and relationship with psychoeducational variables: An international perspectiveVicente E. Caballo and Isabel C. Salazar............................................................................3ArticlesDo School-Based Accommodations Mitigate Anxiety-Related School Impairment for Socially Anxious Youth?Sophie R. Martel, Marissa M. Falcone, Rebecca G. Etkin, Carla E. Marin,Eli R. Lebowitz y Wendy K. Silverman...........................................................................7Impact of School Transition Stressors on Hispanic Adolescents’ Symptoms of Social Anxiety and Depression: Repetitive Negative Thinking as a Potential MediatorAnnette M. La Greca y Evan T. Burdette.........................................................................23Social anxiety profiles and academic self-attributions in secondary school students. What are we really talking about? Theoretical, methodological, and statisticalDori J. A. Urbán, José M. García-Fernández, Aitana Fernández-Sogorb y Candido J. Ingles................................................................................43Adolescents’ interpersonal cognition and self-appraisal of their own anxiety in an imagined anxiety-provoking classroom presentation scenario: Gender differencesKlaus Ranta, Mauri Inkinen, Eero Laakkonen, Hanna-Riitta Ståhl, Niina Junttila y Päivi M. Niemi .......................................................................................572 Relationship between Social Anxiety Symptoms and Behavioral Impairment in Adolescents: The Moderating Role of Perfectionism and Learning MotivationSatoko Sasagawa y Cecilia A. Essau................................................................................79The predictive ability of school refusal on high social anxiety in Chilean adolescentsMariola Giménez-Miralles, Nelly Lagos-San Martín y Carolina Gonzálvez.........................................................97A qualitative study of social anxiety and impairment amid the COVID-19 pandemic for adolescents and young adults in Portugal and the USSamantha Coyle, PhD, Paula Vagos, PhD, Carrie Masia Warner, PhD, Joana Silva, PhD, Ana Xavier, PhD, Grace Martin, Jessica Wimmer,Avi Kalver, Britney Jeyanayagam, Helen-Maria Lekas, PhD, Ana Ganho-Ávila, Luiza Lima & Ana Santos Henrique .......................................................................................115